2018
DOI: 10.1021/acsanm.8b01696
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Halide Ligands in PbS Colloidal Quantum Dots for Field-Effect Transistors and Solar Cells

Abstract: Capping colloidal quantum dots (CQDs) with atomic ligands is a powerful approach to tune their properties and improve the charge carrier transport in CQD solids. Efficient passivation of the CQD surface, which can be achieved with halide ligands, is crucial for application in optoelectronic devices. Heavier halides, i.e., I– and Br–, have been thoroughly studied as capping ligands in the last years, but passivation with fluoride ions has not received sufficient consideration. In this work, effective coating of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 43 publications
5
67
0
2
Order By: Relevance
“…The BA-functionalized CQD films showed shorter PL lifetime than did OA-capped CQD films (Fig. 2d ), which may be attributed to exciton dissociation via charge or energy transfer caused by the enhanced inter-dot coupling 31 , 32 . The EDT-exchanged film showed a substantially reduced PL lifetime compared to the BA-functionalized CQD films.…”
Section: Resultsmentioning
confidence: 97%
“…The BA-functionalized CQD films showed shorter PL lifetime than did OA-capped CQD films (Fig. 2d ), which may be attributed to exciton dissociation via charge or energy transfer caused by the enhanced inter-dot coupling 31 , 32 . The EDT-exchanged film showed a substantially reduced PL lifetime compared to the BA-functionalized CQD films.…”
Section: Resultsmentioning
confidence: 97%
“…[59] Thus, treatment with short ligands such as 3-mercaptopropionic acid (MPA), 1,2-ethanedithiol (EDT), or with atomic halide ligands is essential to fabricating junction-type thin-film QD solar cells. [15,60,61] In 2008, Luther et al reported Schottky solar cells based on EDT-treated PbSe QDs between Indiumdoped tin oxide (ITO) and a metal electrode. [14] Atomic ligand treatment based on an organic ammonium halide salt was later introduced by Tang et al [62] This atomic ligand results in a much shorter interdot distance with improved mobilities compared with short organic ligands.…”
Section: Basic Device Architecture For Carrier Transport In Qd Pvsmentioning
confidence: 99%
“…[ 59 ] Thus, treatment with short ligands such as 3‐mercaptopropionic acid (MPA), 1,2‐ethanedithiol (EDT), or with atomic halide ligands is essential to fabricating junction‐type thin‐film QD solar cells. [ 15,60,61 ] In 2008, Luther et al. reported Schottky solar cells based on EDT‐treated PbSe QDs between Indium‐doped tin oxide (ITO) and a metal electrode.…”
Section: Electrical Design For Qd Pvsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, colloidal quantum dots (QDs) have been widely explored for various applications, including photovoltaics (PV), [1][2][3][4] field-effect transistors, [5,6] light-emitting diodes, [7][8][9] and other solar energy conversion applications. [10][11][12][13][14] Due to their quantum-confinement effect, QDs have size-tunable band gaps that, depending on material and size, can range from the ultraviolet (UV) to near-infrared (NIR).…”
Section: Introductionmentioning
confidence: 99%